Perbedaan Hasil Pewarnaan Hematoxylin Eosin (HE) Pada Histologi Kulit Mencit (Mus Musculus) Berdasarkan Ketebalan Pemotongan 3 Μm, 6 Μm Dan 9 Μm - Nazhiifah, Tristania Shofi; Sofyanita, Eko Naning (Borneo Journal of Medical Laboratory Technology, 2023)
Sectioning is a step that must be passed before staining Hematoxylin Eosin (HE). The aim of this study was to determine differences in the results of Hematoxylin Eosin (HE) staining in mice skin histology (Mus musculus) based on the thickness of the microtome sections of 3 μm, 6 μm, and 9 μm. Experimental research, true experimental research design post test only control group design. The research sample was mice skin preparations (Mus musculus). Primary data collection, cutting of skin preparations using a microtome and staining Hematoxylin Eosin (HE). Field readings were carried out at 400x magnification (40x objective). Data was processed using Kruskal Wallis and Man Whitney. The average value of 6 μm nuclear cutting was 1.44, cytoplasm was 1.15 and color uniformity was 3. The results showed an abnormal distribution, the Kruskal Wallis test (p=0.008) there was a difference in the quality of staining in the 3 μm, 6 μm and 9 μm. The Man Whitney test for the 3 μm and 6 μm microtome cutting groups (p=0.412) showed no difference in the group, the 6 μm and 9 μm microtome cutting groups (p=0.004) there were differences in the group, the 3 μm and 9 μm cutting groups ( p=0.004) there was a difference in the cutting group. The conclusion of this study was that 6 μm microtome cutting produced preparations with better staining quality compared to 3 μm and 9 μm microtome cutting.